Pengaruh Penggunaan Model Pembelajaran TPS Berbantuan Video Pembelajaran Terhadap Hasil Belajar Siswa - Siti Rahmani yanti; Khairil Iba Ibrahim (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the influence of science learning outcomes by using the TPS (Think, Pair, Share) learning model assisted by learning videos on class V students at SDN Lubang Buaya 08 . This research uses a quantitative approach with a Quasi Experimental method type Posttest-Only Control Group Design. The population in this study was all class V students at SDN Lubang Buaya 08 in the even semester of the 2021-2022 academic year. The study sample totaled 64 learners from classes V-B and V-C. This sampling technique uses the Cluster Random Sampling method. The research instrument is in the form of an objective test of multiple-choice questions consisting of 40 questions. The instrument was first tested in class V-D with a total of 32 learners. The calculation of the validity test uses the Correlation Point Biserial formula on 40 questions in multiple choice form with the results of 27 valid questions and 13 drop questions. Meanwhile, in the reliability test using KR-21, it obtained a rhitung of 0.84 with a high level of reliable interpretation. Furthermore, there is a test of the analysis requirements carried out, namely the normality test with the lilliefors formula, which obtained normally distributed data from the experimental class and the control class. Furthermore, a homogeneity test calculation was carried out using the Fisher test which obtained homogeneous distribution group variance homogeneously distributed Then, the hypothesis test using the t-test resulted in a calculation of 4,138 with a significant 5% resulting in the rejection of H0. The results of this study can be concluded that there is an influence of the TPS (Think, Pair, Share) learning model assisted by learning videos on Science Learning Outcomes at SDN Lubang Buaya 08. Keyword: TPS, Learning Videos, Science, Learning Outcomes